High-throughput optical sensing of peri-cellular oxygen in cardiac cells: system characterization, calibration, and testing - Li, Weizhen; McLeod, David; Ketzenberger, John T.; Kowalik, Grant; Russo, Rebekah; Li, Zhenyu; Kay, Matthew W.; Entcheva, Emilia (Frontiers in Bioengineering and Biotechnology, 2023)
Human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) represent a scalable experimental model relevant to human physiology. Oxygen consumption of hiPSC-CMs has not been studied in high-throughput (HT) format plates used in pre-clinical studies. Here, we provide comprehensive characterization and validation of a system for HT long-term optical measurements of peri-cellular oxygen in cardiac syncytia (human iPSC-CM and human cardiac fibroblasts), grown in glass-bottom 96-well plates. Laser-cut oxygen sensors having a ruthenium dye and an oxygen-insensitive reference dye were used. Ratiometric measurements (409nm excitation) reflected dynamic changes in oxygen, as validated with simultaneous Clark electrode measurements. Emission ratios (653nm vs. 510nm) were calibrated for percent oxygen using two-point calibration. Time-dependent changes in the Stern-Volmer parameter, Ksv, were observed during the initial 40-90 min of incubation, likely temperature-related. Effects of pH on oxygen measurements were negligible in the pH range of 4 to 8, with a small ratio reduction for pH>10. Time-dependent calibration was implemented, and light exposure time was optimized (0.6 to 0.8s) for oxygen measurements inside an incubator. Peri-cellular oxygen dropped to levels < 5% within 3 - 10 hours for densely-plated hiPSC-CMs in glass-bottom 96-well plates. After the initial oxygen decrease, samples either settled to low steady-state or exhibited intermittent peri-cellular oxygen dynamics. Cardiac fibroblasts showed slower oxygen depletion and higher steady-state levels without oscillations, compared to hiPSC-CMs. Overall, the system has great utility for long-term HT monitoring of peri-cellular oxygen dynamics in vitro for tracking cellular oxygen consumption, metabolic perturbations, and characterization of the maturation of hiPSC-CMs.